M5 Lung function and psychological well-being: One-year outcomes in severe asthma. (14th November 2013) - Satherley, R; Fellows, J; Mitchell, V; Mansur, AH
Abstract : Aims: Psychological comorbidity and impaired quality of life (QoL) are commonly reported in severe and difficult to treat asthma. These factors appear to contribute to asthma attacks and hospital admissions. Changes in these markers over one-year were studied following multidisciplinary intervention. Research Design and Methods: All new referrals to the Severe and Brittle Asthma Unit (SBAU), between 2009 and 2012 were assessed using a structured protocol including asthma diagnosis and severity, associated co-morbidities, lung function, QoL and drivers of poor asthma control. Patients received multidisciplinary interventions over a one-year period and outcomes were reassessed. Measures used included the Hospital Anxiety and Depression Scale (HADS) and the Juniper QoL. Lung function measures included FEV1 and the Asthma Control Questionnaire. Paired T-Tests and Multiple Regressions were used to analyse the data. Results: 142 patients (N = 108, 76.06% female) completed the baseline measures. After one-year of multidisciplinary intervention 66 completed the HADS, 69 completed the Juniper QoL and 102 had FEV1 reassessed. The majority (N = 96; 85.71%) of these patients met the criteria for refractory asthma. The number of patients on antidepressants significantly decreased over the year from 17.61% (N = 25) to 10.71% (N = 12; p = 0.021). Depression on the HADS showed a non-significant reduction from 53.5% (N = 76) to 42.4% (N = 28; p = .192) after one year. Anxiety on the HADS showed clinically significant reduction from 57.7% (N = 82) to 40.9% (N = 27; p = 0.023). Significant increases in QoL (p = 0.002) were also found on the Juniper QoL. FEV1 significantly improved with a mean score of 2.21 at baseline, increasing to 2.83 at one-year (p < 0.001). Multiple regressions showed that 25% of the variance in QoL was predicted by FEV1 ; however, depression and FEV1 combined explained 50.8% of the variance (p < 0.001). Conclusions: Multidisciplinary intervention led to effective improvement in well-being and lung function in patients with severe and difficult asthma. The improvements in QoL were predicted by both FEV1 and depression. We recommend supporting patients' adaptation to life with severe asthma as an integrated function of the multidisciplinary approach. This approach can help minimise anxiety and depression symptoms, improve QoL and reduce the psychological impact upon physical symptoms.